Review of the monograph’ Konovalova Yu.A. “Russia-India: cooperation in the XXI century” - Gusakov, N.P. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Ėkonomika, 2018)
Review is dedicated to the actual Monograph “Russia-India: cooperation in the XXI century”, that concerned the questions of the modern cooperation between Russian Federation and India Republic. It needs to underline the importance of such investigation due to the fact that it has the practical and theoretical significance not only for the educational process but for the process of implementation and development of Russian and Indian trade and economic cooperation. The Monograph covers key theoretical approaches to the developing countries, founded for the purpose to explain and understand backwardness of such countries. Some strategies were developed as the attempts to overcome such low level of development. The author proved that during the process of transition “from import replacement to export orientation” the government of India realized “unconventional” transfer of development from agriculture sector to service sector with the basis of the government power and industrialization. The author determined that the growing of India’s share in the international trade was based on development of fixed points that were revealed at the process of transition “from import replacement to export orientation”. The character of USSR-India cooperation was determined as an effective with the dominating of Indiadirectional vector. The author considered the key directions of Russia-India trade and economic cooperation at present time, and proposed some recommendations for the purpose of its development and improvement.